(untitled) (Medicine Today, 2021)
Introduction: Pancytopenia is a clinical condition, which refers to a combination of anaemia, leucopenia and thrombocytopenia. It often poses diagnostic challenge to physician and the knowledge of accurate etiologies of this condition is crucial in the management of the patient. Materials and Methods: The study was a prospective study done over a period of October 2011 to December 2011 and 50 patients were evaluated clinically along with haematological parameters, bone marrow aspiration and wherever required, a trephine biopsy was performed in Haematology department of Armed forces institute of pathology (AFIP), Dhaka cantonment, Dhaka. In all patients, a detailed relevant history along with a physical examination was done and data was collected using pre designed proforma. Results: Among the 50 cases studied, age of the patients ranged from 3 to 80 yrs with a mean age of 37.5 yrs and male predominance. Fever and generalized weakness were the most common symptoms. The commonest physical findings were pallor followed by splenomegaly and hepatomegaly. Anisopoikilocytosis and relative lymphocytosis was the most prominent peripheral blood findings in patients. The commonest cause of pancytopenia was Aplastic anaemia (36%), followed by Myelodysplastic syndrome (18%), visceral leishmaniasis (12%), Megaloblastic anaemia (8%), Acute leukaemia (6%), Myelofibrosis (4%), Multiple myeloma (4%), Hypersplenism (4%), Malaria (2%). Conclusion: As a large number of pancytopenic patients have a reversible aetiology, early & proper diagnosis may be life saving. Maximum diagnostic yield can be achieved by correlation with clinical findings & laboratory parameters. Medicine Today 2021 Vol.33(1): 12-18